The Effects of Effective Communication on Employee Performance: A Case Study of Tororo Cement Limited Tororo District - Aketch Betty (Uganda Christian University, 2024)
This study evaluated the Effect of effective Communication on Employee Performance in Tororo Cement Limited. The study objectives included: to analyze the relationship between communication medium on employee performance, to examine awareness between parties influence employee performance with an organization, and assess communication direction influence employee performance. Related literature of different authors on the objectives of the study was also reviewed. Findings revealed that Tororo Cement Limited as an organization involve in relationship between communication medium on employee performance through observation, question based and media methods which help them to discover who the target market is and what those employees think about the product and service before it becomes available to the public. The awareness between parties influence employees’ performance within the organization that it has created untrustworthy between employees and staff members, power imbalance within the organization, frequent supervision and other findings as indicated chapter four. While communication direction influence employee performance by creating competition among staff members and employees, workers productivity decreases because of poor salary payments, physical environment and many other influences. The study recommended that in order to improve on the employee performance in Tororo cement limited there should improve on their management through working on or checking various issues and their weaknesses. They should improve on the working conditions of their workers and increase their wages as well so that they become motivated. Resultantly, the employees will be able to acquire good wages, improve on their standard of living and work willingly, effectively, and efficiently, and further accomplish their duties as expected and encourage willingness to respond to any further study.